Implementation of lean technique 5S at corrugated fiberboard carton industry - Yogeswaran Manikam (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
In organizational development, process improvement is a series of actions taken to identify, analyze and improve existing processes within an organization to meet new goals and objectives. Therefore, implementation of 5S is a must for a safer and healthier working environment within company. 5S is a combination of 5 items which are sort, sort in order, shine, standardizing and self-discipline.